Mapping cortical and subcortical asymmetries in substance dependence: Findings from the ENIGMA Addiction Working Group. (28th January 2021) - Cao, Zhipeng; Ottino‐Gonzalez, Jonatan; Cupertino, Renata B.; Schwab, Nathan; Hoke, Colin; Catherine, Orr; Cousijn, Janna; Dagher, Alain; Foxe, John J.; Goudriaan, Anna E.; Hester, Robert; Hutchison, Kent; et al.
Abstract: Brain asymmetry reflects left‐right hemispheric differentiation, which is a quantitative brain phenotype that develops with age and can vary with psychiatric diagnoses. Previous studies have shown that substance dependence is associated with altered brain structure and function. However, it is unknown whether structural brain asymmetries are different in individuals with substance dependence compared with nondependent participants. Here, a mega‐analysis was performed using a collection of 22 structural brain MRI datasets from the ENIGMA Addiction Working Group. Structural asymmetries of cortical and subcortical regions were compared between individuals who were dependent on alcohol, nicotine, cocaine, methamphetamine, or cannabis ( n  = 1, 796) and nondependent participants ( n  = 996). Substance‐general and substance‐specific effects on structural asymmetry were examined using separate models. We found that substance dependence was significantly associated with differences in volume asymmetry of the nucleus accumbens (NAcc; less rightward; Cohen's d  = 0.15). This effect was driven by differences from controls in individuals with alcohol dependence (less rightward; Cohen's d  = 0.10) and nicotine dependence (less rightward; Cohen's d  = 0.11). These findings suggest that disrupted structural asymmetry in the NAcc may be a characteristic of substance dependence. Abstract : A mega‐analysis with 22 datasets from the ENIGMA Addiction Working Group was performed. Structural asymmetries of cortical and subcortical regions were compared between individuals who were dependent on alcohol, nicotine, cocaine, methamphetamine, or cannabis ( n = 1, 796) and nondependent participants ( n = 996). Less rightward asymmetry of the nucleus accumbens was observed in participants with substance dependence as compared with nondependent participants, suggesting that disrupted structural asymmetry in the nucleus accumbens may be a characteristic of substance dependence.